Breast Tuberculosis: Case report and review literature (Research, Society and Development, 2024)
Introduction: Extrapulmonary manifestations of tuberculosis are well documented, however breast tuberculosis is a rare site of involvement, as it represents 0.1% of breast diseases in developed countries and 3%-4% in endemic countries. Methodology: The present study refers to a case report of Breast Tuberculosis and a literature review carried out in the PUBMED database with the keywords “Breast Tuberculosis” and “Young Adult” in the last 10 years. Case Report: A 32-year-old female patient complained of painful nodules in her right breast, in addition to the growth of axillary lymph nodes, associated with constitutional symptoms. Afterwards, a histopathological puncture of the lesion was requested, which showed the presence of active tuberculosis, and a regimen was initiated. of standard antibiotic therapy. Discussion: Breast tissue is extremely resistant to the presence of Mycobacterium tuberculosis, however these characteristics can change physiologically. The clinical presentation is not very specific with the possibility of breast nodulation being painful or painless, with fistulation or retraction of the breast and formation of a local abscess. Therefore, the gold standard for diagnosis is Fine Needle Aspiration Cytology (FNAC), which can be associated with additional tests. The basis of treatment for breast tuberculosis is antibiotic therapy, with emphasis on ethambutol, pyrazinamide, rifampicin and isoniazid. Conclusion: Breast tuberculosis is one of the differential diagnoses of breast nodulations, with investigation by Fine Needle Aspiration Cytology (FNAC) in addition to other tests that assist in clinical reasoning that leads to appropriate therapy.